2009
DOI: 10.1007/s00402-008-0801-9
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing versus nonresurfacing the patella in total knee arthroplasty: a critical appraisal of the available evidence

Abstract: A systematic literature search for evidences comparing treatment effect and harm of resurfacing versus nonresurfacing the patella in total knee arthroplasty was conducted and yielded five meta-analysis (MA), one systematic review (SR) and six randomized controlled trials not included in previous MAs/SR. The evidence suggests that patellar resurfacing would reduce the risk of anterior knee pain, as well as the risk of patella-related reoperation. Furthermore, patients not undergoing patella resurfacing would ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 54 publications
1
48
0
4
Order By: Relevance
“…Similarly, the meta-analyses from the past decade failed to stratify their data based on the patellofemoral articulation of the implants [3,8,13,[21][22][23]. Specifically, the metaanalysis by Bourne and Burnett [3] noted, ''not resurfacing the patella might be considered in selected younger patients (\ 60 years) with mild or no patellar arthritis, a welltracking extensor mechanism, and particularly if a patellafriendly femoral component is used,'' but data on different patellofemoral designs did not appear in their publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the meta-analyses from the past decade failed to stratify their data based on the patellofemoral articulation of the implants [3,8,13,[21][22][23]. Specifically, the metaanalysis by Bourne and Burnett [3] noted, ''not resurfacing the patella might be considered in selected younger patients (\ 60 years) with mild or no patellar arthritis, a welltracking extensor mechanism, and particularly if a patellafriendly femoral component is used,'' but data on different patellofemoral designs did not appear in their publication.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, numerous randomized controlled trials [1, 5-7, 9, 17, 19, 20, 24, 28, 31] (Table 1) and meta-analyses [3,8,13,[21][22][23] (Table 2) have examined the question of whether surgeons should always resurface the patella at the index TKA or not resurface the patella as a bicompartmental knee arthroplasty (BKA). Most of the recent randomized controlled trials [1, 5-7, 9, 19, 24] reported no difference in BKA versus TKA outcome measures, including Knee Society clinical rating score and reoperation rate, while others point to TKA superiority [17,20,28,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have been published with similar clinical and functional outcomes, with or without patellar resurfacing [1,5,20,21]. In addition, several complications after resurfacing such as patella fracture, dislocation or avascular necrosis have been reported [3].…”
Section: Introductionmentioning
confidence: 93%
“…However, because the category of reoperation mixed any operation for any reason and the confounders could affect the comparison of revision of the patellofemoral joint between patellar resurfacing and patellar nonresurfacing. We further divided reoperation into two categories for subgroup analysis [29]. Boyd et al [7] reported that most complications occurred after the third or fourth year postoperatively, and based on this factor we categorised primary outcomes as short term (under five years) or mid-to long term(over five years) for subgroup analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%